2021
DOI: 10.3390/ani11030906
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Microbiological and Technological Properties of Red Deer (Cervus elaphus) Milk during Lactation

Abstract: This study describes chemical, physical, microbiological and technological characteristics of red deer milk and the effect of lactation on these parameters in order to know their potential aptitude to elaborate dairy products. During 18 weeks, milk from five hinds was monitored for composition, bacteriology, somatic cell count (SCC), physical properties and rennet coagulation. Mean values (g/100 g) for fat, protein, lactose and dry matter were 10.4, 7.1, 4.3 and 24.2, respectively, and for urea, 265 mg/100 mL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 65 publications
3
6
0
Order By: Relevance
“…The proximate compositions of the deer milk and their lactational trends were mostly consistent with those reported previously [ 1 , 2 , 5 , 6 , 8 ], although the lactose content of the deer milk in the present study was at the higher end of the reported range. Increases in protein and fat contents and decreases in lactose content towards the end of lactation have also been reported for the milks of other ruminants (cow, sheep, and goat) [ 14 , 19 , 23 , 24 ].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The proximate compositions of the deer milk and their lactational trends were mostly consistent with those reported previously [ 1 , 2 , 5 , 6 , 8 ], although the lactose content of the deer milk in the present study was at the higher end of the reported range. Increases in protein and fat contents and decreases in lactose content towards the end of lactation have also been reported for the milks of other ruminants (cow, sheep, and goat) [ 14 , 19 , 23 , 24 ].…”
Section: Resultssupporting
confidence: 92%
“…Red deer ( Cervus elaphus ) are domesticated primarily for meat, velvet, leather, and hunting purposes [ 1 , 2 ]. New Zealand is one of the leading countries in deer farming.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations